DEVELOPMENT OF MATHEMATICS TEACHING MATERIAL BASED ON REALISTIC MATHEMATICS EDUCATION IN ELEMENTARY SCHOOL - Siti Halimah; Lia Kurniawati (JIP Jurnal Ilmiah PGMI, 2022)
This study aims to develop teaching material based on Realistic Mathematics Education (RME) on fractions for grade 4 students in elementary schools so as to produce teaching material that is valid and practical to use in learning. This type of research is Research and Development (R&D). Research applies the ADDIE development model which consists of 5 stages suc as analysis, design, development, implementation, and evaluation. This research is conducted at Islamic Elementary School of Raudhah BSD Palembang. Based on the results of validation by material experts that the development of realistic mathematics teaching material based on mathematics education is considered valid with a high score of 88.63%. The results of the validation by media experts were also considered valid with a high score of 87.22%. This teaching material also has practical value as the results of the product test on students obtained a high score of 91.94%. This research proves that the development of mathematics teaching material based on realistic mathematics education is very feasible and practical to use in learning mathematics in elementary school.